Insider threats - Arduin, Pierre-Emmanuel (London : ISTE Ltd. ; Hoboken, NJ : John Wiley & Sons, Inc., 2018)
An information system may be regarded as an organized set of resources, both technological and human. Security should take this specificity into consideration in order to ensure an overall security of information systems. The security of information systems is usually tackled in a technological perspective. This book proposes to focus not only on information systems' security in a technological perspective, but also in a human, managerial and organizational perspective.
1. Information Systems 1.1. The technological point of view -- managing computers 1.2. The Human point of view -- managing individuals 2. Security 2.1. The technological view of Information System's security 2.1. The Human view of Information System's security 3. Classifying attacks and managing countermeasures.
Online resource; title from PDF title page (EBSCO, viewed March 26, 2018).
Includes bibliographical references and index.
Keywords: Computer security; Computer networks -- Security measures; COMPUTERS -- Internet -- Security; COMPUTERS -- Networking -- Security; COMPUTERS -- Security -- General; Computer networks -- Security measures; Computer security; Electronic books